Why is this pattern irrefulable? - haskell

I'm new to Haskell and trying to create a function that evaluates an arithmetic expression:
data Expr = Number Rational | Variable String | Plus Expr Expr deriving (Eq, Show , Read)
eval (Plus lhs rhs) = Number (a + b)
where Number a = eval lhs
Number b = eval rhs
eval x = x
main = putStrLn . show $ eval (Plus (Number 1) (Variable "x"))
I want the eval function to evaluate the expression until it hits a Variable, meaning whenever the two expressions within Plus evaluate to a Number you can collapse it to a new Number, otherwise you cannot collapse the Plus but maybe you can collapse only one side of the Plus. eg: eval (Plus (Number a) (Number b)) == Number (a + b) eval (Plus (Var "a") b) == Plus (Var "a") (eval b)
I expected the pattern Number b to fail and to move on to eval x = x
and just return the expression as is, but instead it produces an error:
main: main.hs:5:9-27: Irrefutable pattern failed for pattern Main.Number b
Why is this happening and how can I solve it ?

You will want to use a case expression to match all the possible outcomes of the inner eval calls, not just Numbers:
eval (Plus lhs rhs) = case (eval lhs, eval rhs) of
(Number a, Number b) -> Number (a + b) -- two numbers can be summed
(otherA, otherB) -> Plus otherA otherB -- other values form a Plus with collapsed parts
eval x = x

You can use ViewPatterns to make this relatively pretty:
{-# LANGUAGE ViewPatterns #-}
eval (Plus (eval -> Number a) (eval -> Number b)) = Number (a+b)
eval x = x
Given your comments, I would be remiss if I didn't point out there are some flaws with your proposed algorithm, though; for example:
> eval (Number 3 `Plus` Number 4 `Plus` Variable "a") -- doesn't know about associativity of Plus
Plus (Plus (Number (3 % 1)) (Number (4 % 1))) (Variable "a")
> eval (Variable "a" `Plus` (Number 3 `Plus` Number 4)) -- doesn't simplify recursively when it hits a variable
Plus (Variable "a") (Plus (Number (3 % 1)) (Number (4 % 1)))
Consider normalizing to a less structured type; perhaps something like
data Sum = Sum Rational (MultiSet String)
telling the sum of all the Numbers in the first part and how often each variable appeared in the second part. Then
eval :: Expr -> Sum
eval (Number r) = Sum r empty
eval (Variable v) = Sum 0 (singleton v)
eval (Plus l r) = Sum (r+r') (union vs vs') where
Sum r vs = eval l
Sum r' vs' = eval r

Related

Haskell - arithmetic operations with datatypes

I was writing my own haskell datatype to resolve a sum operation with integers, but i dont know how to make the semantic .
data Expr = Value Int
| Sum Expr Expr
I was trying to do:
sum:: Expr -> Expr -> Int
sum a b = b + a
val:: Int -> Int
val a = a
I want to write like:
Sum (Value 3) (Value 5)
And get 8 as return, any ideas?
Typically, in this sort of situation, you write an "evaluator" or "interpreter" -- a single function that accepts an Expr and evaluates it to a value:
eval :: Expr -> Int
Then, you can write:
> eval (Sum (Value 3) (Value 5))
8
>
Haskell's pattern matching for function definitions makes this very elegant:
eval (Value x) = ...
eval (Sum e1 e2) = ...you'll need to use eval recursively here...
So, instead of writing multiple functions, one for each component of your Expr, you write a single function with one pattern-based definition for each component.
If this was homework, you might want to stop here and try to figure the details out for yourself. If it wasn't, then the following should work:
eval :: Expr -> Int
eval (Value x) = x
eval (Sum e1 e2) = eval e1 + eval e2
You need to define sum appropriately for each combination of data constructors.
sum :: Expr -> Expr -> Int
sum (Value x) (Value y) = x + y
sum (Sum a b) (Sum c d) = sum a b + sum c d
sum (Value x) (Sub a b) = x + sum a b
sum (Sum a b) (Value y) = sum a b + y
This can be simplified; one way is with a helper function that reduces a single Expr to an integer value first.
value :: Expr -> Int
value (Value x) = x
value (Sum x y) = (value x) + (value y)
sum :: Expr -> Expr -> Int
sum x y = value x + value y

Reference data from function

I have those info on my haskell code:
data Symtable a = General a | Stack a
class Evaluable e where
eval :: (Num a, Ord a) => (Ident -> Maybe a) -> (e a) -> (Either String a)
typeCheck :: (Ident -> String) -> (e a) -> Bool
instance (Num a, Ord a) => Evaluable (NExpr a) where
eval f f2 = Left ("Undefined variable: ") --to make the code compilable
typeCheck f f2 = True --to make the code compilable
The thing is, eval function returns the evaluation of a numeric expression (for example 3 + 5, or x + 3), therefore I have to check the value of X on the symtable data but I haven't got it referenced on this function (I cannot edit the function header). How can I do it?
ident = string and Nexpr:
data NExpr n = Const n |
Var Ident |
Plus (NExpr n) (NExpr n) |
Minus (NExpr n) (NExpr n) |
Times (NExpr n) (NExpr n)
The first arugment to eval is a function that will look up the value of a name found in an expression. You ignore it when evaluating a Const value, use it when evaluating a Var value, and just pass it along to the recursive calls for the other cases.
instance (Num a, Ord a) => Evaluable (NExpr a) where
eval _ (Const n) = Right n
eval lookup (Var x) = case lookup x of
Nothing -> Left ("Undefined variable: " ++ x)
Just y -> Right y
eval lookup (Plus left right) = (+) <$> eval lookup left <*> eval lookup right
-- etc

Reusing patterns in pattern guards or case expressions

My Haskell project includes an expression evaluator, which for the purposes of this question can be simplified to:
data Expression a where
I :: Int -> Expression Int
B :: Bool -> Expression Bool
Add :: Expression Int -> Expression Int -> Expression Int
Mul :: Expression Int -> Expression Int -> Expression Int
Eq :: Expression Int -> Expression Int -> Expression Bool
And :: Expression Bool -> Expression Bool -> Expression Bool
Or :: Expression Bool -> Expression Bool -> Expression Bool
If :: Expression Bool -> Expression a -> Expression a -> Expression a
-- Reduces an Expression down to the simplest representation.
reduce :: Expression a -> Expression a
-- ... implementation ...
The straightforward approach to implementing this is to write a case expression to recursively evaluate and pattern match, like so:
reduce (Add x y) = case (reduce x, reduce y) of
(I x', I y') -> I $ x' + y'
(x', y') -> Add x' y'
reduce (Mul x y) = case (reduce x, reduce y) of
(I x', I y') -> I $ x' * y'
(x', y') -> Mul x' y'
reduce (And x y) = case (reduce x, reduce y) of
(B x', B y') -> B $ x' && y'
(x', y') -> And x' y'
-- ... and similarly for other cases.
To me, that definition looks somewhat awkward, so I then rewrote the definition using pattern guards, like so:
reduce (Add x y) | I x' <- reduce x
, I y' <- reduce y
= I $ x' + y'
I think this definition looks cleaner compared to the case expression, but when defining multiple patterns for different constructors, the pattern is repeated multiple times.
reduce (Add x y) | I x' <- reduce x
, I y' <- reduce y
= I $ x' + y'
reduce (Mul x y) | I x' <- reduce x
, I y' <- reduce y
= I $ x' * y'
Noting these repeated patterns, I was hoping there would be some syntax or structure that could cut down on the repetition in the pattern matching. Is there a generally accepted method to simplify these definitions?
Edit: after reviewing the pattern guards, I've realised they don't work as a drop-in replacement here. Although they provide the same result when x and y can be reduced to I _, they do not reduce any values when the pattern guards do not match. I would still like reduce to simplify subexpressions of Add et al.
One partial solution, which I've used in a similar situation, is to extract the logic into a "lifting" function that takes a normal Haskell operation and applies it to your language's values. This abstracts over the wrappping/unwrapping and resulting error handling.
The idea is to create two typeclasses for going to and from your custom type, with appropriate error handling. Then you can use these to create a liftOp function that could look like this:
liftOp :: (Extract a, Extract b, Pack c) => (a -> b -> c) ->
(Expression a -> Expression b -> Expression c)
liftOp err op a b = case res of
Nothing -> err a' b'
Just res -> pack res
where res = do a' <- extract $ reduce' a
b' <- extract $ reduce' b
return $ a' `op` b'
Then each specific case looks like this:
Mul x y -> liftOp Mul (*) x y
Which isn't too bad: it isn't overly redundant. It encompasses the information that matters: Mul gets mapped to *, and in the error case we just apply Mul again.
You would also need instances for packing and unpacking, but these are useful anyhow. One neat trick is that these can also let you embed functions in your DSL automatically, with an instance of the form (Extract a, Pack b) => Pack (a -> b).
I'm not sure this will work exactly for your example, but I hope it gives you a good starting point. You might want to wire additional error handling through the whole thing, but the good news is that most of that gets folded into the definition of pack, unpack and liftOp, so it's still pretty centralized.
I wrote up a similar solution for a related (but somewhat different) problem. It's also a way to handle going back and forth between native Haskell values and an interpreter, but the interpreter is structured differently. Some of the same ideas should still apply though!
This answer is inspired by rampion's follow-up question, which suggests the following function:
step :: Expression a -> Expression a
step x = case x of
Add (I x) (I y) -> I $ x + y
Mul (I x) (I y) -> I $ x * y
Eq (I x) (I y) -> B $ x == y
And (B x) (B y) -> B $ x && y
Or (B x) (B y) -> B $ x || y
If (B b) x y -> if b then x else y
z -> z
step looks at a single term, and reduces it if everything needed to reduce it is present. Equiped with step, we only need a way to replace a term everywhere in the expression tree. We can start by defining a way to apply a function inside every term.
{-# LANGUAGE RankNTypes #-}
emap :: (forall a. Expression a -> Expression a) -> Expression x -> Expression x
emap f x = case x of
I a -> I a
B a -> B a
Add x y -> Add (f x) (f y)
Mul x y -> Mul (f x) (f y)
Eq x y -> Eq (f x) (f y)
And x y -> And (f x) (f y)
Or x y -> Or (f x) (f y)
If x y z -> If (f x) (f y) (f z)
Now, we need to apply a function everywhere, both to the term and everywhere inside the term. There are two basic possibilities, we could apply the function to the term before applying it inside or we could apply the function afterwards.
premap :: (forall a. Expression a -> Expression a) -> Expression x -> Expression x
premap f = emap (premap f) . f
postmap :: (forall a. Expression a -> Expression a) -> Expression x -> Expression x
postmap f = f . emap (postmap f)
This gives us two possibilities for how to use step, which I will call shorten and reduce.
shorten = premap step
reduce = postmap step
These behave a little differently. shorten removes the innermost level of terms, replacing them with literals, shortening the height of the expression tree by one. reduce completely evaluates the expression tree to a literal. Here's the result of iterating each of these on the same input
"shorten"
If (And (B True) (Or (B False) (B True))) (Add (I 1) (Mul (I 2) (I 3))) (I 0)
If (And (B True) (B True)) (Add (I 1) (I 6)) (I 0)
If (B True) (I 7) (I 0)
I 7
"reduce"
If (And (B True) (Or (B False) (B True))) (Add (I 1) (Mul (I 2) (I 3))) (I 0)
I 7
Partial reduction
Your question implies that you sometimes expect that expressions can't be reduced completely. I'll extend your example to include something to demonstrate this case, by adding a variable, Var.
data Expression a where
Var :: Expression Int
...
We will need to add support for Var to emap:
emap f x = case x of
Var -> Var
...
bind will replace the variable, and evaluateFor performs a complete evaluation, traversing the expression only once.
bind :: Int -> Expression a -> Expression a
bind a x = case x of
Var -> I a
z -> z
evaluateFor :: Int -> Expression a -> Expression a
evaluateFor a = postmap (step . bind a)
Now reduce iterated on an example containing a variable produces the following output
"reduce"
If (And (B True) (Or (B False) (B True))) (Add (I 1) (Mul Var (I 3))) (I 0)
Add (I 1) (Mul Var (I 3))
If the output expression from the reduction is evaluated for a specific value of Var, we can reduce the expression all the way to a literal.
"evaluateFor 5"
Add (I 1) (Mul Var (I 3))
I 16
Applicative
emap can instead be written in terms of an Applicative Functor, and postmap can be made into a generic piece of code suitable for other data types than expressions. How to do so is described in this answer to rampion's follow-up question.

Conversion from lambda term to combinatorial term

Suppose there are some data types to express lambda and combinatorial terms:
data Lam α = Var α -- v
| Abs α (Lam α) -- λv . e1
| App (Lam α) (Lam α) -- e1 e2
deriving (Eq, Show)
infixl 0 :#
data SKI α = V α -- x
| SKI α :# SKI α -- e1 e2
| I -- I
| K -- K
| S -- S
deriving (Eq, Show)
There is also a function to get a list of lambda term's free variables:
fv ∷ Eq α ⇒ Lam α → [α]
fv (Var v) = [v]
fv (Abs x e) = filter (/= x) $ fv e
fv (App e1 e2) = fv e1 ++ fv e2
To convert lambda term to combinatorial term abstract elimination rules could be usefull:
convert ∷ Eq α ⇒ Lam α → SKI α
1) T[x] => x
convert (Var x) = V x
2) T[(E₁ E₂)] => (T[E₁] T[E₂])
convert (App e1 e2) = (convert e1) :# (convert e2)
3) T[λx.E] => (K T[E]) (if x does not occur free in E)
convert (Abs x e) | x `notElem` fv e = K :# (convert e)
4) T[λx.x] => I
convert (Abs x (Var y)) = if x == y then I else K :# V y
5) T[λx.λy.E] => T[λx.T[λy.E]] (if x occurs free in E)
convert (Abs x (Abs y e)) | x `elem` fv e = convert (Abs x (convert (Abs y e)))
6) T[λx.(E₁ E₂)] => (S T[λx.E₁] T[λx.E₂])
convert (Abs x (App y z)) = S :# (convert (Abs x y)) :# (convert (Abs x z))
convert _ = error ":["
This definition is not valid because of 5):
Couldn't match expected type `Lam α' with actual type `SKI α'
In the return type of a call of `convert'
In the second argument of `Abs', namely `(convert (Abs y e))'
In the first argument of `convert', namely
`(Abs x (convert (Abs y e)))'
So, what I have now is:
> convert $ Abs "x" $ Abs "y" $ App (Var "y") (Var "x")
*** Exception: :[
What I want is (hope I calculate it right):
> convert $ Abs "x" $ Abs "y" $ App (Var "y") (Var "x")
S :# (S (KS) (S (KK) I)) (S (KK) I)
Question:
If lambda term and combinatorial term have a different types of expression, how 5) could be formulated right?
Let's consider the equation T[λx.λy.E] => T[λx.T[λy.E]].
We know the result of T[λy.E] is an SKI expression. Since it has been produced by one of the cases 3, 4 or 6, it is either I or an application (:#).
Thus the outer T in T[λx.T[λy.E]] must be one of the cases 3 or 6. You can perform this case analysis in the code. I'm sorry but I don't have the time to write it out.
Here it's better to have a common data type for combinators and lambda expressions. Notice that your types already have significant overlap (Var, App), and it doesn't hurt to have combinators in lambda expressions.
The only possibility we want to eliminate is having lambda abstractions in combinator terms. We can forbid them using indexed types.
In the following code the type of a term is parameterised by the number of nested lambda abstractions in that term. The convert function returns Term Z a, where Z means zero, so there are no lambda abstractions in the returned term.
For more information about singleton types (which are used a bit here), see the paper Dependently Typed Programming with Singletons.
{-# LANGUAGE DataKinds, KindSignatures, TypeFamilies, GADTs, TypeOperators,
ScopedTypeVariables, MultiParamTypeClasses, FlexibleInstances #-}
data Nat = Z | Inc Nat
data SNat :: Nat -> * where
SZ :: SNat Z
SInc :: NatSingleton n => SNat n -> SNat (Inc n)
class NatSingleton (a :: Nat) where
sing :: SNat a
instance NatSingleton Z where sing = SZ
instance NatSingleton a => NatSingleton (Inc a) where sing = SInc sing
type family Max (a :: Nat) (b :: Nat) :: Nat
type instance Max Z a = a
type instance Max a Z = a
type instance Max (Inc a) (Inc b) = Inc (Max a b)
data Term (l :: Nat) a where
Var :: a -> Term Z a
Abs :: NatSingleton l => a -> Term l a -> Term (Inc l) a
App :: (NatSingleton l1, NatSingleton l2)
=> Term l1 a -> Term l2 a -> Term (Max l1 l2) a
I :: Term Z a
K :: Term Z a
S :: Term Z a
fv :: Eq a => Term l a -> [a]
fv (Var v) = [v]
fv (Abs x e) = filter (/= x) $ fv e
fv (App e1 e2) = fv e1 ++ fv e2
fv _ = []
eliminateLambda :: (Eq a, NatSingleton l) => Term (Inc l) a -> Term l a
eliminateLambda t =
case t of
Abs x t ->
case t of
Var y
| y == x -> I
| otherwise -> App K (Var y)
Abs {} -> Abs x $ eliminateLambda t
App a b -> S `App` (eliminateLambda $ Abs x a)
`App` (eliminateLambda $ Abs x b)
App a b -> eliminateLambdaApp a b
eliminateLambdaApp
:: forall a l1 l2 l .
(Eq a, Max l1 l2 ~ Inc l,
NatSingleton l1,
NatSingleton l2)
=> Term l1 a -> Term l2 a -> Term l a
eliminateLambdaApp a b =
case (sing :: SNat l1, sing :: SNat l2) of
(SInc _, SZ ) -> App (eliminateLambda a) b
(SZ , SInc _) -> App a (eliminateLambda b)
(SInc _, SInc _) -> App (eliminateLambda a) (eliminateLambda b)
convert :: forall a l . Eq a => NatSingleton l => Term l a -> Term Z a
convert t =
case sing :: SNat l of
SZ -> t
SInc _ -> convert $ eliminateLambda t
The key insight is that S, K and I are just constant Lam terms, in the same way that 1, 2 and 3 are constant Ints. It would be pretty easy to make rule 5 type-check by making an inverse to the 'convert' function:
nvert :: SKI a -> Lam a
nvert S = Abs "x" (Abs "y" (Abs "z" (App (App (Var "x") (Var "z")) (App (Var "y") (Var "z")))))
nvert K = Abs "x" (Abs "y" (Var "x"))
nvert I = Abs "x" (Var "x")
nvert (V x) = Var x
nvert (x :# y) = App (nvert x) (nvert y)
Now we can use 'nvert' to make rule 5 type-check:
convert (Abs x (Abs y e)) | x `elem` fv e = convert (Abs x (nvert (convert (Abs y e))))
We can see that the left and the right are identical (we'll ignore the guard), except that 'Abs y e' on the left is replaced by 'nvert (convert (Abs y e))' on the right. Since 'convert' and 'nvert' are each others' inverse, we can always replace any Lam 'x' with 'nvert (convert x)' and likewise we can always replace any SKI 'x' with 'convert (nvert x)', so this is a valid equation.
Unfortunately, while it's a valid equation it's not a useful function definition because it won't cause the computation to progress: we'll just convert 'Abs y e' back and forth forever!
To break this loop we can replace the call to 'nvert' with a 'reminder' that we should do it later. We do this by adding a new constructor to Lam:
data Lam a = Var a -- v
| Abs a (Lam a) -- \v . e1
| App (Lam a) (Lam a) -- e1 e2
| Com (SKI a) -- Reminder to COMe back later and nvert
deriving (Eq, Show)
Now rule 5 uses this reminder instead of 'nvert':
convert (Abs x (Abs y e)) | x `elem` fv e = convert (Abs x (Com (convert (Abs y e))))
Now we need to make good our promise to come back, by making a separate rule to replace reminders with actual calls to 'nvert', like this:
convert (Com c) = convert (nvert c)
Now we can finally break the loop: we know that 'convert (nvert c)' is always identical to 'c', so we can replace the above line with this:
convert (Com c) = c
Notice that our final definition of 'convert' doesn't actually use 'nvert' at all! It's still a handy function though, since other functions involving Lam can use it to handle the new 'Com' case.
You've probably noticed that I've actually named this constructor 'Com' because it's just a wrapped-up COMbinator, but I thought it would be more informative to take a slightly longer route than just saying "wrap up your SKIs in Lams" :)
If you're wondering why I called that function "nvert", see http://unapologetic.wordpress.com/2007/05/31/duality-terminology/ :)
Warbo is right, combinators are constant lambda terms, consequently the conversion function is
T[ ]:L -> C with L the set of lambda terms and C that of combinatory terms and with C ⊂ L .
So there is no typing problem for the rule T[λx.λy.E] => T[λx.T[λy.E]]
Here an implementation in Scala.

Calculating expressions modulo n

When doing calculations modulo n with large numbers, you will encounter huge performency penalties when doing for example mod (123456789^987654321) n. Instead you have to use your own ^ that internally calculates mod n also for intermedite calculations.
Sure, I can easily implement my own functions, but then I have to explicitly say "mod n" for each operation. Instead one could build an numeric expression tree and defer actual calculations, and in the end state modulo n only once. (see my code below)
I started on this to clearly show what I mean, but I wonder if there already exists implementations of this, it seems quite useful so somebody ought to have implemented it.
module Modulo where
data Expr =
V Integer
| Plus Expr Expr
| Mult Expr Expr
deriving (Eq, Show)
instance Num Expr where
(+) = Plus
(*) = Mult
fromInteger = V
eval :: Integer -> Expr -> Integer
eval m (V i) = i `mod` m
eval m (Plus e1 e2) = (eval m e1 + eval m e2) `mod` m
eval m (Mult e1 e2) = (eval m e1 * eval m e2) `mod` m
fifteen :: Expr
fifteen = 10 + 5
test = eval 13 fifteen
Oleg did something of this kind, where you make an instance for modulo arithmetic, but for a arbitrary modulus. Implicit configurations.

Resources